In threat of co-extinction: two new species of Acizzia Heslop-Harrison (Hemiptera: Psyllidae) from vulnerable species of Acacia and Pultenaea - Taylor, Gary S.; Moir, Melinda L. (Zootaxa, 2009)
Two new species of Acizzia, A. veski, sp. nov. and A. keithi, sp. nov. are described from the vulnerable or threatened plant species respectively, Acacia veronica Maslin (Fabaceae: Mimosoideae), with a restricted distribution in the southwest of Western Australia and Pultenaea glabra Benth. (Fabaceae: Faboideae), with a restricted distribution in eastern Australia. Pultenaea is recorded here as a new host genus record for Acizzia. Both new species of Acizzia are considered at risk of extinction as they have been recorded only from single localities on vulnerable or threatened hosts with restricted distributions.